MANAGEMENT OF MULTI DRUG RESISTANT IN TREATMENT OF GONORRHEA : A SYSTEMATIC REVIEW - Yulianto, Ronald; Aristika Gunawan, Ellen (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: A significant worldwide public health issue, gonorrhea is made worse by antibiotic resistance.Aims : This systematic review is to review the treatment of gonorrhea in patients with multi drug resistant  of antimicroba.Methods: This study demonstrated compliance with all requirements by means of a comparison with the standards established by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020. Thus, the specialists were able to guarantee that the research was as current as feasible. Publications released between 2014 and 2024 were considered for this search strategy. This was accomplished by utilizing a number of distinct online reference sites, including Pubmed, ScienceDirect, and SagePub. It was determined that reviews, previously published works, and partially completed works would not be included. Result: In the PubMed database, the results of our search brought up 4.511 articles, whereas the results of our search on SCIENCE DIRECT brought up 1.110 articles, our search on SAGEPUB brought up 1.738 articles. The results of the search conducted for the last year of 2014 yielded a total 1.464 articles for PubMed, 265 articles for SCIENCE DIRECT and 684 articles for SAGEPUB. In the end, we compiled a total of  5 papers, 3 of which came from PubMed, 1 of which came from SCIENCE DIRECT and 1 of which came from SAGEPUB. We included five research that met the criteria.Conclusion: In summary, globally, the prevalence of gonococcal infections is growing quickl. Most concerningly, N. gonorrhoeae is a significant contributor to the bacterial population that disseminates resistance to antibiotics.